1996
DOI: 10.1021/ja9532749
|View full text |Cite
|
Sign up to set email alerts
|

Solvent and Distance Dependent Charge Separation in Rigid Trichromophoric Systems

Abstract: Disclaimer/Complaints regulationsIf you believe that digital publication of certain material infringes any of your rights or (privacy) interests, please let the Library know, stating your reasons. In case of a legitimate complaint, the Library will make the material inaccessible and/or remove it from the website. Please Ask the Library: http://uba.uva.nl/en/contact, or a letter to: Library of the University of Amsterdam, Secretariat, Singel 425, 1012 WP Amsterdam, The Netherlands. You will be contacted as soon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
63
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 30 publications
0
63
0
Order By: Relevance
“…For the spectroscopy of the title compound and its preparation, see: Chen et al (2006). For the spectroscopy and electronic device applications of rigid oligo-norbornyl compounds, see: Chen et al (2002); Chow et al (2005); Lewis et al (1997); Roest et al (1996). For related structures, see: Ç elik et al (2006); Chiou et al (2001); Chow et al (1999); Lough et al (2006).…”
Section: Related Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For the spectroscopy of the title compound and its preparation, see: Chen et al (2006). For the spectroscopy and electronic device applications of rigid oligo-norbornyl compounds, see: Chen et al (2002); Chow et al (2005); Lewis et al (1997); Roest et al (1996). For related structures, see: Ç elik et al (2006); Chiou et al (2001); Chow et al (1999); Lough et al (2006).…”
Section: Related Literaturementioning
confidence: 99%
“…Financial support from the National Science Council of the Republic of China is gratefully acknowledged. attracted considerable attention due to their potential applications in the design of molecular devices (Lewis et al, 1997;Roest et al, 1996). Numerous types of spacers have been reported (Chiou et al, 2001;Chow et al, 1999).…”
Section: Data Collectionmentioning
confidence: 99%
“…or,c an control charge-separationa nd charge-recombination processes, and this has ad irect effect on the photocurrent responses. [40][41][42][43][44][45][46] In this work, it is hoped that this methodf or DNA-scaffolded chromophore-aggregate constructionc an be extendedt ot hree-components ystemsi no rder to efficiently generatep hotocurrents. Furthermore, in this study it is shown that at hree-component systemu sing the oligo-T aggregates of the diphenyldiketopyrrolopyrrole (PDPP) derivative( 3 in Scheme1)c an enhance the photocurrent generation efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7][8][9][10][11][12][13][14] The challenge and long-range goal behind this concept is firstly, to promote efficient intramolecular energy or electron-transfer reaction and/or, secondly, to generate long-lived charge-separated states, [15][16][17][18][19] and thirdly to enhance the light-harvesting efficiency. Fortunately fullerene derives have shown excellent three-dimensional electron acceptors and possess small reorganization energy of electron transfer, which lead to remarkable acceleration of photo-induced charge separation and charge shift and deceleration of charge recombination.…”
Section: Introductionmentioning
confidence: 99%